Degenerative lumbar spinal canal stenosis surgery by endoscopy approach - Eshkulov Dostonjon Ilkhomovich; Khujanazarov Ilkhom Eshkulovich (International Journal of Medical Sciences And Clinical Research, 2025)
Lumbar degenerative spinal canal stenosis (LDSS) is a prevalent condition that significantly impacts the quality of life of patients, leading to substantial economic costs in the healthcare system. It is commonly observed in individuals aged over 50 and is primarily caused by degenerative disc disease. Traditional treatment options, including laminectomy, come with potential complications, including nerve damage, infection, and prolonged recovery times. An emerging alternative is percutaneous spinal lumbar decompression (PSLD), a minimally invasive procedure that aims to reduce these complications while improving clinical outcomes. Methods: The study was conducted at the Republican Center of Traumatology and Orthopedics in Uzbekistan from 2020 to 2025. A total of 50 patients diagnosed with lumbar spinal stenosis were included in the analysis. The patients were divided into two groups: the endoscopic PSLD group (n=27) and the traditional decompressive surgery group (n=23). All patients underwent preoperative assessments using radiography, multislice computed tomography (MSCT), and magnetic resonance imaging (MRI) to evaluate spinal canal dimensions, foraminal opening size, and the severity of stenosis. Visual Analog Scale (VAS) used for evaluation of pain. Statistical analyses, including t-tests and chi-square tests, were used to compare outcomes between the two groups, with a significance level set at p<0.05. Results: The mean age of patients in the endoscopic PSLD group was 56.86 ± 7.7 years, and in the traditional surgery group, it was 54.25 ± 5.08 years, with no significant difference observed between the two groups in terms of age. Postoperatively, the mean VAS score for the traditional surgery group was 3.8 (SD=0.96), while for the endoscopic PSLD group, it was significantly lower at 2.51 (SD=1.01), indicating that the PSLD group experienced significantly less postoperative pain (p<0.05). Conclusion: This study demonstrates that endoscopic PSLD is a promising alternative to traditional decompressive surgery for the treatment of lumbar stenosis. The procedure offers significant advantages in terms of postoperative pain relief and reduced recovery time, making it a favorable option for patients.